Open Versus Transanal Pull-Through for Hirschsprung Disease: A Systematic Review of Long-Term Outcome - Gosemann, Jan-Hendrik; Friedmacher, Florian; Ure, Benno; Lacher, Martin (European Journal of Pediatric Surgery, 2013)
Introduction Various surgical techniques for the treatment of Hirschsprung disease (HD) have been proposed. The most relevant long-term complications of HD surgery include constipation, soiling/incontinence, enterocolitis, and anastomotic stricture. To date, there has been no randomized controlled trial evaluating the long-term outcome of OPEN surgery compared with transanal approaches with and without laparoscopy (laparoscopic-assisted transanal-endorectal pull-through [L-TERPT] and transanal-endorectal pull-through [TERPT]). We performed a systematic literature review of the long-term outcome of OPEN surgery compared with L-TERPT/TERPT.Methods Our systematic review of the recent literature (2008 to 2012) included reports on long-term outcome of either OPEN surgery or L-TERPT/TERPT with a minimum follow-up period of 12 months. With the cumulative data, a comparative meta-analysis was performed for the outcome parameters “constipation,” “soiling/incontinence,” “enterocolitis,” and “anastomotic stricture.”Results Functional outcome of surgical techniques for HD was highly variable. We could show a significant advantage of L-TERPT/TERPT over OPEN surgery regarding the incidence of soiling/incontinence and constipation. No differences were seen for enterocolitis and anastomotic stricture.Conclusion Significant differences in the long-term outcome of OPEN surgery compared with L-TERPT/TERPT were identified in this review. We conclude from our data that L-TERPT/TERPT represents a valid option in the treatment of HD and might have some advantages over the OPEN techniques. However, the present data should be interpreted carefully due to limitations in the quality of the study design in most reports. Prospective, randomized, multicenter trials are urgently needed to overcome this weakness of the current literature.
Keywords: Hirschsprung; pull-through; outcome; open surgery; transanal surgery